1999
DOI: 10.1021/jf990449f
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins, Phenolics, and Color of Cabernet Franc, Merlot, and Pinot Noir Wines from British Columbia

Abstract: Changes in phenolics (anthocyanins, flavonols, tartaric esters, and total phenolics) during ripening of grapes and in phenolics and color during vinification and aging of Cabernet Franc, Merlot, and Pinot Noir wines were studied. Anthocyanins in grape skins showed variations in accumulation pattern, concentration, and distribution depending on variety and to a lesser extent on season. During vinification, colorless phenolics increased during alcoholic fermentation, reached maximum values at pressing, and remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
342
1
14

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 518 publications
(389 citation statements)
references
References 9 publications
32
342
1
14
Order By: Relevance
“…Outra hipótese é que o solvente utilizado no método de Francis (1982) não garante a total extração de antocianinas, pois o metanol é 20 % mais eficiente que o etanol e 73 % mais eficiente que a água, em termos de extração de antocianinas (METIVIER et al, 1980). O teor de antocianinas monoméricas (76,2 ± 0,3 %) e poliméricas (22,9 ± 0,4 %) encontrado neste estudo está dentro do esperado para amostras com elevado conteúdo de antocianinas, como previsto para sucos e vinhos (9,2 a 36,0 % poliméricas) (HAGER et al, 2008;MAZZA et al, 1999). Como esperado, o resultado obtido para antocianinas copigmentadas, 1,6 ± 0,1 %, não foi representativo comparando com valores obtidos em vinho de uvas Cabernet Franc, Merlot e Pinot Noir (32,4 a 51,6 %) reportados por Mazza et al (1999).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Outra hipótese é que o solvente utilizado no método de Francis (1982) não garante a total extração de antocianinas, pois o metanol é 20 % mais eficiente que o etanol e 73 % mais eficiente que a água, em termos de extração de antocianinas (METIVIER et al, 1980). O teor de antocianinas monoméricas (76,2 ± 0,3 %) e poliméricas (22,9 ± 0,4 %) encontrado neste estudo está dentro do esperado para amostras com elevado conteúdo de antocianinas, como previsto para sucos e vinhos (9,2 a 36,0 % poliméricas) (HAGER et al, 2008;MAZZA et al, 1999). Como esperado, o resultado obtido para antocianinas copigmentadas, 1,6 ± 0,1 %, não foi representativo comparando com valores obtidos em vinho de uvas Cabernet Franc, Merlot e Pinot Noir (32,4 a 51,6 %) reportados por Mazza et al (1999).…”
Section: Resultsunclassified
“…O teor de antocianinas monoméricas (76,2 ± 0,3 %) e poliméricas (22,9 ± 0,4 %) encontrado neste estudo está dentro do esperado para amostras com elevado conteúdo de antocianinas, como previsto para sucos e vinhos (9,2 a 36,0 % poliméricas) (HAGER et al, 2008;MAZZA et al, 1999). Como esperado, o resultado obtido para antocianinas copigmentadas, 1,6 ± 0,1 %, não foi representativo comparando com valores obtidos em vinho de uvas Cabernet Franc, Merlot e Pinot Noir (32,4 a 51,6 %) reportados por Mazza et al (1999). No presente es-O pico 4b foi identificado como fitoeno, considerando os espectros UV-visível (l máx e estrutura fina) e de massas.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…General increases in berry, must, and wine phenols and anthocyanins from Merlot and Cabernet Sauvignon cluster thinning treatments were confirmed by Di Profio et al (2011a,b) and Mazza et al (1999). Positive effects of cluster thinning on Pinot noir wines were reported by Reynolds et al (1996), while Guidoni et al (2002) found increased soluble solids, skin anthocyanins, and flavonoids in cluster-thinned Nebbiolo grapes.…”
mentioning
confidence: 78%
“…A uva apresenta teores fenólicos totais de 5-8% nas sementes, 1-4% no engaço e 1-2% na casca (SHRIKHANDE, 2000). Além disso, nas cascas, encontram-se flavonoides, tais como antocianinas, flavonóis, flavonóis e proantocianidinas, e não flavonoides, tais como ácidos fenólicos e estilbenos (MAZZA, 1995;MAZZA et al, 1999;MONTEALEGRE et al, 2006;PERESTRELO et al, 2012). Por outro lado, nas sementes, ocorrem predominantemente os taninos condensados.…”
Section: Introductionunclassified